THE CRIMINOLOGY OF GENOCIDE REFLECTIONS ON CRIMINAL RESPONSIBILITY OF LUIS ECHEVERRÍA IN DIRTY WAR CRIMES - García Huitrón, Alan (2024)
The objective of the article was to reflect, from criminology, on the role of former Mexican president Luis Echeverria in the forced disappearance of Rosendo Radilla Pacheco that occurred in 1974. Based on a documentary analysis of the figure of the military chain of command and the situational, structural and intersubjective context of the Mexican Army during the era known as the Dirty War, it was possible to demonstrate that Echeverría, the former Secretary of National Defense and other leaders section and military zones acted as part of a criminal enterprise in order to carry out a structured plan aimed at eradicating - outside the rule of law - everything that was, seemed, supported or sympathized with the sheaves (term used for those people who sought to modify social conditions within a horizon of justice).